Efect of age regrowth and nitrogen fertilization on the nutritive value of Brachiaria brizantha cv. "Marandú" - Gándara, Luis; Borrajo, Celina I.; Fernández, Juan A.; Pereira, M. Mercedes (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
In Brachiaria brizantha cv. Marandú, it was evaluated the nutritional value. Nutritional value was considered: crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and in vitro digestibility of dry matter (IVDDM). The variables were evaluated for age of regrowth (28, 56, 84 and 112 days) and fertilization (F0, F1, F2, F3 and F4). We determined the nutritional value. CP content showed interaction between age and fertilization. Nitrogen fertilization can increase the proportion of PB. The average values of regrowth age were 46, 48, 60, 71, and 77 g CP kg DM-1 to F1, F2, F3, F4 and F5 respectively. It was a positive answer to fertilization (627-645 g NDF kg DM-1 to F1 and F4) and age (567-683 g kg DM-1 from 28 to 112 days). In turn, fertilization had no effect on the ADF and if there was a positive response from the age of regrowth, with average values of 278 to 399 g kg DM-1 ADF at 28 and 112 days respectively. The IVDDM was affected by the age ranging from 603 to 370 g kg DM-1 from 28 days to 112 days. Age regrowth is the most important factor in the nutritional value.